PENGARUH KOMPENSASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PERUSAHAAN PT. CAMPUS DATA MEDIA (CDM) SEMARANG - Pramudho Sasmito Adhi, 07.05.51.0094; Isnowati, Sri (Students Journal of Economic and Management, 2013)
The purpose of the study entitled "The Effect of compensation and leadership style on job satisfaction of employees on company PT. Campus Data Media (CDM) semarang "is to analyze compensation and leadership style on job satisfaction towards PT. Campus Data Media (CDM) Semarang. The sample used in this study were 76 respondents. Sampling technique in this study using census sampling technique to the data collection methods used in this research is using questionnaires (questionnaire) by spreading a list of questions to respondents in order to obtain information. The collected data were analyzed using factor analysis to test the validity of the item, the Cronbach alpha formula to test the reliability of the instrument, regression analysis, to examine the influence of each partial independent variables were tested with the coefficient of determination and test fit the model to test and prove the influence of the Partial each independent variable. The results of the hypothesis are: (1) The results of the statistical linear regression analysis can be shown by the regression equation Y = 0.362 + 0.527 X1 X2. Standardized coefficients (standardized Coefficients) in the table above, are used to determine the effect of independent variables, namely: leadership style (X1), compensation (X2), employee satisfaction (Y) PT. Campus Media Data. (2) The calculation of Adjusted R Square coefficient of determination is equal to 0756 or by 75.6%. This means that the effect of leadership style variable (X1), variable compensation (X2) jointly influence the job satisfaction variable (Y) is equal to 75.6% while the remaining 24.4% is influenced by other variables not included in the study. (3) The hypothesis that has been done in this study we can conclude that: A) There is a positive and significant effect of leadership style on employee job satisfaction. B) There is a positive and significant effect on job satisfaction employee compensation. C) Compensation and leadership styles together has a positive and significant effect on job satisfaction. Keywords: leadership style, compensation and job satisfaction